Register awareness and English language learning: the case of multi-word discourse markers - Liu, Li-E. (2013)
Research in L2 learners' use of discourse markers (DMs), which largely focuses on single-word DMs and reports learners' overuse or underuse tendency, generally concludes that L2 learners need a keener register awareness in this regard. This lack of awareness in using DMs in accordance with the appropriate register, however, is not further pursued. Although extensive studies have been carried out in examining multi-word discourse markers (MDMs), researchers have exclusively focused on the formulaic nature of these MDMs. The linking nature that MDMs possess has been largely neglected. This thesis therefore aims to explore further the pragmatic awareness of L2 learners in their use of MDMs by including both corpus-based studies and experiments. Questions to be addressed include to what extent L2 learners exert their pragmatic awareness and use MDMs appropriately, and whether or not English proficiency affects the types and quantities of MDMs used by learners. The thesis first describes the usage patterns of the targeted MDMs in 4 native speaker (NS) corpora, leading to the creation of a formality continuum along which various MDMs can be placed. An additional investigation in the Cambridge Learner Corpus (CLC) shows that the overuse/underuse phenomenon has to be discussed by taking into account the semantic categories of MDMs. Two studies - the reaction time (RT) task and the multiple discourse completion task (MDCT) - are carried out with the goals of perceiving learners' pragmatic awareness and testing whether the learners' corpus-based results can be supported by the experimental data. The results show that advanced L2 learners notice the embedded formality mismatch better than the intermediate learners. The L2 participants in the two studies find identifying Concessive links the most difficult and this is supported by the fact that CLC learners also show a lack of register awareness in using Concessive MDMs. Future work includes applying the methodology to other multi-word units, recruiting different groups of L2 learners (ESL), and pursuing the thesis's implication for teaching.